Improving forecasts of GARCH family models with the artificial neural networks: An application to the daily returns in Istanbul Stock Exchange - Bildirici, Melike; Ersin, Oezguer Oemer (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In the study, we discussed the ARCH/GARCH family models and enhanced them with artificial neural networks to evaluate the volatility of daily returns for 23.10.1987-22.02.2008 period in Istanbul Stock Exchange. We proposed ANN-APGARCH model to increase the forecasting performance of APGARCH model. The ANN-extended versions of the obtained GARCH models improved forecast results. It is noteworthy that daily returns in the ISE show strong volatility clustering, asymmetry and nonlinearity characteristics. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Volatility; Stock returns; ARCH/GARCH; EGARCH; TGARCH; PGARCH; APGARCH; Artificial neural networks; AUTOREGRESSIVE CONDITIONAL HETEROSCEDASTICITY; S-AND-P; PERCEPTRON; VARIANCE; Computer Science; Engineering; Operations Research & Management Science